2018
DOI: 10.1002/ejp.1206
|View full text |Cite
|
Sign up to set email alerts
|

Randomized double‐blind controlled study of bedtime low‐dose amitriptyline in chronic neck pain

Abstract: This randomized controlled trial is the first to show the effectiveness and tolerance of a medication, low-dose amitriptyline, in managing idiopathic chronic neck pain and its related comorbidities. The optimal treatment of this condition was still controversial in the literature. It extends the indication of low-dose amitriptyline to another chronic pain condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…A post hoc sensitivity analysis explored the effect of removing one trial from the pooled estimates for back pain 59. The participants in this trial had neck pain, received a dose of amitriptyline (5 mg/day) lower than the minimum dose recommended for pain relief (10-25 mg/day), and reported unexpectedly large improvements in pain and disability compared with other studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A post hoc sensitivity analysis explored the effect of removing one trial from the pooled estimates for back pain 59. The participants in this trial had neck pain, received a dose of amitriptyline (5 mg/day) lower than the minimum dose recommended for pain relief (10-25 mg/day), and reported unexpectedly large improvements in pain and disability compared with other studies.…”
Section: Resultsmentioning
confidence: 99%
“…Large, definitive trials free of industry ties are urgently needed to evaluate the efficacy of antidepressants. In our review, all but one trial59 with sample sizes of more than 100 participants in each group were sponsored by industry. New trials will be particularly relevant when testing the efficacy of TCAs and SNRIs in people with sciatica, where clinically important benefits might exist; and in osteoarthritis, where clinically important benefits cannot be excluded but most of the data come from industry sponsored trials 484950515258…”
Section: Discussionmentioning
confidence: 99%
“…Because of worse tolerability, the doses of amitriptyline used in painful patients are classically initiated at 5–10 mg/day (e.g. Maarrawi et al., ) and are lower than those used for depressed patients (starting dose = 50–75 mg/day). These arguments should be taken into consideration for future trials.…”
Section: Discussionmentioning
confidence: 99%
“…Among available and established pharmacological treat ments, antidepressants are effective in different chronic musculoskeletal pain conditions associated with central sensitisation, such as fibromyalgia, 81 low back pain, 82 neck pain, 83 and knee osteoarthritis. 84 A syste matic review found moderate to high quality evidence that the anti convulsant gabapentin is ineffective for the treatment of low back pain or lumbar radicular pain, 85 whereas another systematic review found insuffi cient evidence to either support or refute the efficacy of gabapentin in reducing pain in patients with fibromyalgia.…”
Section: Can Central Sensitisation Be Treated In Patients With Chronimentioning
confidence: 99%